Freemasonic and Orange Order Membership in Rural Ontario During the Late 19th-century: A Micro-Study - Klages, Gregory (Ontario History, 2011)
This study tests observations regarding the dynamics of fraternal organizations in urban and semi-urban Ontario communities against those in a rural settlement. The study focuses on Freemasonic and Orange Lodges that operated in a southwestern Ontario town of less than 2,000 persons between the late 1860s and the early 1900s. Exceptional results indicate fraternal organizations operating in rural Ontario during the late nineteenth century may have had some unique characteristics. Further study could test the wider applicability of these results and serve to shed further light on the role of fraternal organizations in community- and identity-building in rural Ontario during this period.